Theory Abacus_Hoare
section ‹Hoare Rules for Abacus Programs›
theory Abacus_Hoare
imports Abacus
begin
type_synonym abc_assert = "nat list ⇒ bool"
definition
assert_imp :: "('a ⇒ bool) ⇒ ('a ⇒ bool) ⇒ bool" (‹_ ↦ _› [0, 0] 100)
where
"assert_imp P Q ≡ ∀xs. P xs ⟶ Q xs"
fun abc_holds_for :: "(nat list ⇒ bool) ⇒ (nat × nat list) ⇒ bool" (‹_ abc'_holds'_for _› [100, 99] 100)
where
"P abc_holds_for (s, lm) = P lm"
fun abc_final :: "(nat × nat list) ⇒ abc_prog ⇒ bool"
where
"abc_final (s, lm) p = (s = length p)"
fun abc_notfinal :: "abc_conf ⇒ abc_prog ⇒ bool"
where
"abc_notfinal (s, lm) p = (s < length p)"
fun abc_out_of_prog :: "abc_conf ⇒ abc_prog ⇒ bool"
where
"abc_out_of_prog (s, lm) p = (length p < s)"
definition abcP_out_of_pgm_ex :: abc_prog
where
"abcP_out_of_pgm_ex = [Dec 0 41, Inc 1, Goto 0]"
lemma "abc_steps_l (0,[5,3]) abcP_out_of_pgm_ex (10 +6) = (41, [0, 8])"
by (simp add: abc_steps_l.simps abc_step_l.simps abc_fetch.simps abc_lm_v.simps abc_lm_s.simps
numeral_eqs_upto_12
abcP_out_of_pgm_ex_def )
lemma "abc_out_of_prog (abc_steps_l (0,[5,3]) abcP_out_of_pgm_ex (10 +6)) abcP_out_of_pgm_ex"
by (simp add: abc_steps_l.simps abc_step_l.simps abc_fetch.simps abc_lm_v.simps abc_lm_s.simps
numeral_eqs_upto_12
abcP_out_of_pgm_ex_def )
lemma "abc_notfinal cf p ∨ abc_final cf p ∨ abc_out_of_prog cf p"
by (metis (full_types) abc_final.elims(3) abc_notfinal.elims(3) abc_out_of_prog.elims(3) not_less_iff_gr_or_eq prod.sel(1))
lemma "⟦ length p ≠ 0; abc_notfinal cf p ⟧ ⟹ ¬ abc_final cf p ∧ ¬ abc_out_of_prog cf p"
by (metis abc_final.simps abc_notfinal.elims(2) abc_out_of_prog.simps less_Suc_eq nat_neq_iff not_less_eq)
lemma "⟦ length p ≠ 0; abc_final cf p ⟧ ⟹ ¬ abc_notfinal cf p ∧ ¬ abc_out_of_prog cf p"
by (metis abc_final.elims(2) abc_final.simps abc_notfinal.elims(2) abc_out_of_prog.simps nat_neq_iff)
lemma "⟦ length p ≠ 0; abc_out_of_prog cf p ⟧ ⟹ ¬ abc_notfinal cf p ∧ ¬ abc_final cf p"
by (metis abc_final.simps abc_notfinal.simps abc_out_of_prog.simps less_iff_Suc_add less_imp_add_positive less_not_refl not_less_eq old.prod.exhaust)
definition
abc_Hoare_halt :: "abc_assert ⇒ abc_prog ⇒ abc_assert ⇒ bool" (‹(⦃(1_)⦄/ (_)/ ⦃(1_)⦄)› 50)
where
"abc_Hoare_halt P p Q ≡ ∀lm. P lm ⟶ (∃n. abc_final (abc_steps_l (0, lm) p n) p ∧ Q abc_holds_for (abc_steps_l (0, lm) p n))"
lemma abc_Hoare_haltI:
assumes "⋀lm. P lm ⟹ ∃n. abc_final (abc_steps_l (0, lm) p n) p ∧ Q abc_holds_for (abc_steps_l (0, lm) p n)"
shows " ⦃P⦄ (p::abc_prog) ⦃Q⦄ "
unfolding abc_Hoare_halt_def
using assms by auto
fun app_mopup :: "tprog0 ⇒ nat ⇒ tprog0"
where
"app_mopup tp n = tp @ shift (mopup_n_tm n) (length tp div 2)"
lemma compile_correct_halt_2:
assumes compile: "tp = tm_of ap"
and abc_halt: "abc_steps_l (0, ns) ap stp = (length ap, am)"
and rs_loc: "n < length am"
shows "∃stp i j. steps0 (Suc 0, [Bk,Bk], <ns::nat list>) (app_mopup tp n) stp = (0, Bk↑i, <abc_lm_v am n> @ Bk↑j)"
proof -
have crsp: "crsp (layout_of ap) (0, ns) (Suc 0, [Bk,Bk], <ns::nat list>) []"
by (auto simp add: start_of.simps crsp.simps)
with assms have "∃ stp i j. steps (Suc 0, [Bk,Bk], <ns::nat list>) (tp @ shift (mopup_n_tm n) (length tp div 2), 0) stp
= (0, Bk↑i @ Bk # Bk # [], Oc↑Suc (abc_lm_v am n) @ Bk↑j)"
using compile_correct_halt by simp
then have "∃stp i j. steps (Suc 0, [Bk,Bk], <ns::nat list>) (tp @ shift (mopup_n_tm n) (length tp div 2), 0) stp
= (0, Bk↑i, Oc↑Suc (abc_lm_v am n) @ Bk↑j)"
by (metis replicate_app_Cons_same replicate_append_same take_suc)
then show ?thesis
by (simp add: tape_of_nat_def)
qed
lemma compile_correct_halt_3:
assumes compile: "tp = tm_of ap"
and abc_halt: "abc_steps_l (0, ns) ap stp = (length ap, am)"
and rs_loc: "n < length am"
shows "∃stp i j. steps0 (Suc 0, [], <ns::nat list>) (app_mopup tp n) stp = (0, Bk↑i, <abc_lm_v am n> @ Bk↑j)"
using steps_left_tape_ShrinkBkCtx_to_NIL compile_correct_halt_2
by (metis abc_halt compile replicate_Suc replicate_once rs_loc take_suc)
lemma compile_correct_halt_4:
assumes compile: "tp = tm_of ap"
and abc_halt: "abc_steps_l (0, ns) ap stp = (length ap, am)"
and rs_loc: "n < length am"
shows "TMC_yields_num_res (app_mopup tp n) ns (abc_lm_v am n)"
unfolding TMC_yields_num_res_def
using compile_correct_halt_3
by (metis One_nat_def abc_halt compile rs_loc)
definition ABC_yields_res :: "abc_prog ⇒ nat list ⇒ nat ⇒ nat ⇒ bool"
where "ABC_yields_res ap ns n r ≡
(∃stp am. abc_steps_l (0, ns) ap stp = (length ap, am) ∧
r < length am ∧ (abc_lm_v am r = n))"
definition ABC_loops_on :: "abc_prog ⇒ nat list ⇒ bool"
where "ABC_loops_on ap ns ≡
∀stp. abc_notfinal (abc_steps_l (0, ns) ap stp) ap"
theorem ABC_yields_res_imp_TMC_yields_num_res:
assumes "tp = tm_of ap"
and "ABC_yields_res ap ns n r"
shows "TMC_yields_num_res (app_mopup tp r) ns n"
proof -
from ‹ABC_yields_res ap ns n r›
have "∃stp am. abc_steps_l (0, ns) ap stp = (length ap, am) ∧
r < length am ∧ (abc_lm_v am r = n)"
unfolding ABC_yields_res_def
by auto
then obtain stp am where
w_stp_am: "abc_steps_l (0, ns) ap stp = (length ap, am) ∧
r < length am ∧ (abc_lm_v am r = n)" by blast
have "TMC_yields_num_res (app_mopup tp r) ns (abc_lm_v am r)"
proof (rule compile_correct_halt_4)
from assms show "tp = tm_of ap" by auto
next
from w_stp_am
show "r < length am"
by auto
next
from w_stp_am
show "abc_steps_l (0, ns) ap stp = (length ap, am)"
by auto
qed
with w_stp_am show "TMC_yields_num_res (app_mopup tp r) ns n" by auto
qed
lemma abc_unhalt_2:
assumes compile: "tp = tm_of ap"
and notfinal: "∀stp. abc_notfinal (abc_steps_l (0, ns) ap stp) ap"
shows "∀stp.¬ is_final (steps0 (Suc 0, [Bk,Bk], <ns::nat list>) (app_mopup tp r) stp)"
proof -
have "∀stp.¬ is_final (steps (1, [Bk,Bk], <ns::nat list>) (tp @ shift (mopup_n_tm r) (length tp div 2), 0) stp)"
proof (rule compile_correct_unhalt)
show "layout_of ap = layout_of ap" by auto
next
from compile show "tp = tm_of ap" by auto
next
show "length tp div 2 = length tp div 2" by auto
next
show "crsp (layout_of ap) (0, ns) (1, [Bk, Bk], <ns::nat list>) []"
by (auto simp add: start_of.simps crsp.simps)
next
from notfinal show " ∀stp. case abc_steps_l (0, ns) ap stp of (as, am) ⇒ as < length ap"
by (metis abc_notfinal.elims(2) case_prodI2 prod.sel(1))
qed
then show ?thesis by auto
qed
theorem ABC_loops_imp_TMC_loops:
assumes "tp = tm_of ap"
and "ABC_loops_on ap ns"
shows "TMC_loops (app_mopup tp r) ns"
proof -
have "∀stp.¬ is_final (steps0 (Suc 0, [Bk,Bk], <ns::nat list>) (app_mopup tp r) stp)"
proof (rule abc_unhalt_2)
from ‹tp = tm_of ap›
show "tp = tm_of ap" by auto
next
from ‹ABC_loops_on ap ns›
show "∀stp. abc_notfinal (abc_steps_l (0, ns) ap stp) ap"
unfolding ABC_loops_on_def by auto
qed
have "∀stp. ¬ is_final (steps0 (Suc 0, [], <ns>) (app_mopup tp r) stp)"
proof
fix stp
show "¬ is_final (steps0 (Suc 0, [], <ns>) (app_mopup tp r) stp)"
proof
assume "is_final (steps0 (Suc 0, [], <ns>) (app_mopup tp r) stp)"
then have "∃ltap rtap. steps0 (Suc 0, Bk ↑0, <ns>) (app_mopup tp r) stp = (0, ltap, rtap)"
using is_final.elims(2) replicate_empty by fastforce
then obtain ltap rtap where
"steps0 (Suc 0, Bk ↑0, <ns>) (app_mopup tp r) stp = (0, ltap, rtap)" by blast
then have "∃z3. z3 ≤ 0 + 2 ∧
steps0 (Suc 0, Bk↑(0 + 2), <ns>) (app_mopup tp r) stp = (0,ltap @ Bk↑z3 ,rtap)"
using steps_left_tape_EnlargeBkCtx_arbitrary_CL
by (metis add.left_neutral add_2_eq_Suc' append_Nil)
then have "is_final (steps0 (Suc 0, [Bk,Bk], <ns>) (app_mopup tp r) stp)"
using One_nat_def add_2_eq_Suc' add_Suc_shift is_finalI length_replicate list.size(3)
list.size(4) plus_1_eq_Suc replicate_Suc replicate_once by force
with ‹∀stp. ¬ is_final (steps0 (Suc 0, [Bk, Bk], <ns>) (app_mopup tp r) stp)›
show False by auto
qed
qed
then show "TMC_loops (app_mopup tp r) ns"
unfolding TMC_loops_def
by simp
qed
definition
abc_Hoare_unhalt :: "abc_assert ⇒ abc_prog ⇒ bool" (‹(⦃(1_)⦄/ (_)) ↑› 50)
where
"abc_Hoare_unhalt P p ≡ ∀args. P args ⟶ (∀n. abc_notfinal (abc_steps_l (0, args) p n) p)"
lemma abc_Hoare_unhaltI:
assumes "⋀args n. P args ⟹ abc_notfinal (abc_steps_l (0, args) p n) p"
shows "⦃P⦄ (p::abc_prog) ↑"
unfolding abc_Hoare_unhalt_def
using assms by auto
fun abc_inst_shift :: "abc_inst ⇒ nat ⇒ abc_inst"
where
"abc_inst_shift (Inc m) n = Inc m" |
"abc_inst_shift (Dec m e) n = Dec m (e + n)" |
"abc_inst_shift (Goto m) n = Goto (m + n)"
fun abc_shift :: "abc_inst list ⇒ nat ⇒ abc_inst list"
where
"abc_shift xs n = map (λ x. abc_inst_shift x n) xs"
fun abc_comp :: "abc_inst list ⇒ abc_inst list ⇒
abc_inst list" (infixl ‹[+]› 99)
where
"abc_comp al bl = (let al_len = length al in
al @ abc_shift bl al_len)"
lemma abc_comp_first_step_eq_pre:
"s < length A
⟹ abc_step_l (s, lm) (abc_fetch s (A [+] B)) =
abc_step_l (s, lm) (abc_fetch s A)"
by(simp add: abc_step_l.simps abc_fetch.simps nth_append)
lemma abc_before_final:
"⟦abc_final (abc_steps_l (0, lm) p n) p; p ≠ []⟧
⟹ ∃ n'. abc_notfinal (abc_steps_l (0, lm) p n') p ∧
abc_final (abc_steps_l (0, lm) p (Suc n')) p"
proof(induct n)
case 0
thus "?thesis"
by(simp add: abc_steps_l.simps)
next
case (Suc n)
have ind: " ⟦abc_final (abc_steps_l (0, lm) p n) p; p ≠ []⟧ ⟹
∃n'. abc_notfinal (abc_steps_l (0, lm) p n') p ∧ abc_final (abc_steps_l (0, lm) p (Suc n')) p"
by fact
have final: "abc_final (abc_steps_l (0, lm) p (Suc n)) p" by fact
have notnull: "p ≠ []" by fact
show "?thesis"
proof(cases "abc_final (abc_steps_l (0, lm) p n) p")
case True
have "abc_final (abc_steps_l (0, lm) p n) p" by fact
then have "∃n'. abc_notfinal (abc_steps_l (0, lm) p n') p ∧ abc_final (abc_steps_l (0, lm) p (Suc n')) p"
using ind notnull
by simp
thus "?thesis"
by simp
next
case False
have "¬ abc_final (abc_steps_l (0, lm) p n) p" by fact
from final this have "abc_notfinal (abc_steps_l (0, lm) p n) p"
by(case_tac "abc_steps_l (0, lm) p n", simp add: abc_step_red2
abc_step_l.simps abc_fetch.simps split: if_splits)
thus "?thesis"
using final
by(rule_tac x = n in exI, simp)
qed
qed
lemma notfinal_Suc:
"abc_notfinal (abc_steps_l (0, lm) A (Suc n)) A ⟹
abc_notfinal (abc_steps_l (0, lm) A n) A"
apply(case_tac "abc_steps_l (0, lm) A n")
apply(simp add: abc_step_red2 abc_fetch.simps abc_step_l.simps split: if_splits)
done
lemma abc_comp_first_steps_eq_pre:
assumes notfinal: "abc_notfinal (abc_steps_l (0, lm) A n) A"
and notnull: "A ≠ []"
shows "abc_steps_l (0, lm) (A [+] B) n = abc_steps_l (0, lm) A n"
using notfinal
proof(induct n)
case 0
thus "?case"
by(simp add: abc_steps_l.simps)
next
case (Suc n)
have ind: "abc_notfinal (abc_steps_l (0, lm) A n) A ⟹ abc_steps_l (0, lm) (A [+] B) n = abc_steps_l (0, lm) A n"
by fact
have h: "abc_notfinal (abc_steps_l (0, lm) A (Suc n)) A" by fact
then have a: "abc_notfinal (abc_steps_l (0, lm) A n) A"
by(simp add: notfinal_Suc)
then have b: "abc_steps_l (0, lm) (A [+] B) n = abc_steps_l (0, lm) A n"
using ind by simp
obtain s lm' where c: "abc_steps_l (0, lm) A n = (s, lm')"
by (metis prod.exhaust)
then have d: "s < length A ∧ abc_steps_l (0, lm) (A [+] B) n = (s, lm')"
using a b by simp
thus "?case"
using c
by(simp add: abc_step_red2 abc_fetch.simps abc_step_l.simps nth_append)
qed
declare abc_shift.simps[simp del] abc_comp.simps[simp del]
lemma halt_steps2: "st ≥ length A ⟹ abc_steps_l (st, lm) A stp = (st, lm)"
apply(induct stp)
by(simp_all add: abc_step_red2 abc_steps_l.simps abc_step_l.simps abc_fetch.simps)
lemma halt_steps: "abc_steps_l (length A, lm) A n = (length A, lm)"
apply(induct n, simp add: abc_steps_l.simps)
apply(simp add: abc_step_red2 abc_step_l.simps nth_append abc_fetch.simps)
done
lemma abc_steps_add:
"abc_steps_l (as, lm) ap (m + n) =
abc_steps_l (abc_steps_l (as, lm) ap m) ap n"
apply(induct m arbitrary: n as lm, simp add: abc_steps_l.simps)
proof -
fix m n as lm
assume ind:
"⋀n as lm. abc_steps_l (as, lm) ap (m + n) =
abc_steps_l (abc_steps_l (as, lm) ap m) ap n"
show "abc_steps_l (as, lm) ap (Suc m + n) =
abc_steps_l (abc_steps_l (as, lm) ap (Suc m)) ap n"
apply(insert ind[of as lm "Suc n"], simp)
apply(insert ind[of as lm "Suc 0"], simp add: abc_steps_l.simps)
apply(case_tac "(abc_steps_l (as, lm) ap m)", simp)
apply(simp add: abc_steps_l.simps)
apply(case_tac "abc_step_l (a, b) (abc_fetch a ap)",
simp add: abc_steps_l.simps)
done
qed
lemma equal_when_halt:
assumes exc1: "abc_steps_l (s, lm) A na = (length A, lma)"
and exc2: "abc_steps_l (s, lm) A nb = (length A, lmb)"
shows "lma = lmb"
proof(cases "na > nb")
case True
then obtain d where "na = nb + d"
by (metis add_Suc_right less_iff_Suc_add)
thus "?thesis" using assms halt_steps
by(simp add: abc_steps_add)
next
case False
then obtain d where "nb = na + d"
by (metis add.comm_neutral less_imp_add_positive nat_neq_iff)
thus "?thesis" using assms halt_steps
by(simp add: abc_steps_add)
qed
lemma abc_comp_first_steps_halt_eq':
assumes final: "abc_steps_l (0, lm) A n = (length A, lm')"
and notnull: "A ≠ []"
shows "∃ n'. abc_steps_l (0, lm) (A [+] B) n' = (length A, lm')"
proof -
have "∃ n'. abc_notfinal (abc_steps_l (0, lm) A n') A ∧
abc_final (abc_steps_l (0, lm) A (Suc n')) A"
using assms
by(rule_tac n = n in abc_before_final, simp_all)
then obtain na where a:
"abc_notfinal (abc_steps_l (0, lm) A na) A ∧
abc_final (abc_steps_l (0, lm) A (Suc na)) A" ..
obtain sa lma where b: "abc_steps_l (0, lm) A na = (sa, lma)"
by (metis prod.exhaust)
then have c: "abc_steps_l (0, lm) (A [+] B) na = (sa, lma)"
using a abc_comp_first_steps_eq_pre[of lm A na B] assms
by simp
have d: "sa < length A" using b a by simp
then have e: "abc_step_l (sa, lma) (abc_fetch sa (A [+] B)) =
abc_step_l (sa, lma) (abc_fetch sa A)"
by(rule_tac abc_comp_first_step_eq_pre)
from a have "abc_steps_l (0, lm) A (Suc na) = (length A, lm')"
using final equal_when_halt
by(case_tac "abc_steps_l (0, lm) A (Suc na)" , simp)
then have "abc_steps_l (0, lm) (A [+] B) (Suc na) = (length A, lm')"
using a b c e
by(simp add: abc_step_red2)
thus "?thesis"
by blast
qed
lemma abc_exec_null: "abc_steps_l sam [] n = sam"
apply(cases sam)
apply(induct n)
apply(auto simp: abc_step_red2)
apply(auto simp: abc_step_l.simps abc_steps_l.simps abc_fetch.simps)
done
lemma abc_comp_first_steps_halt_eq:
assumes final: "abc_steps_l (0, lm) A n = (length A, lm')"
shows "∃ n'. abc_steps_l (0, lm) (A [+] B) n' = (length A, lm')"
using final
apply(case_tac "A = []")
apply(rule_tac x = 0 in exI, simp add: abc_steps_l.simps abc_exec_null)
apply(rule_tac abc_comp_first_steps_halt_eq', simp_all)
done
lemma abc_comp_second_step_eq:
assumes exec: "abc_step_l (s, lm) (abc_fetch s B) = (sa, lma)"
shows "abc_step_l (s + length A, lm) (abc_fetch (s + length A) (A [+] B))
= (sa + length A, lma)"
using assms
apply(auto simp: abc_step_l.simps abc_fetch.simps nth_append abc_comp.simps abc_shift.simps split : if_splits )
apply(case_tac [!] "B ! s", auto simp: Let_def)
done
lemma abc_comp_second_steps_eq:
assumes exec: "abc_steps_l (0, lm) B n = (sa, lm')"
shows "abc_steps_l (length A, lm) (A [+] B) n = (sa + length A, lm')"
using assms
proof(induct n arbitrary: sa lm')
case 0
thus "?case"
by(simp add: abc_steps_l.simps)
next
case (Suc n)
have ind: "⋀sa lm'. abc_steps_l (0, lm) B n = (sa, lm') ⟹
abc_steps_l (length A, lm) (A [+] B) n = (sa + length A, lm')" by fact
have exec: "abc_steps_l (0, lm) B (Suc n) = (sa, lm')" by fact
obtain sb lmb where a: " abc_steps_l (0, lm) B n = (sb, lmb)"
by (metis prod.exhaust)
then have "abc_steps_l (length A, lm) (A [+] B) n = (sb + length A, lmb)"
using ind by simp
moreover have "abc_step_l (sb + length A, lmb) (abc_fetch (sb + length A) (A [+] B)) = (sa + length A, lm') "
using a exec abc_comp_second_step_eq
by(simp add: abc_step_red2)
ultimately show "?case"
by(simp add: abc_step_red2)
qed
lemma length_abc_comp[simp, intro]:
"length (A [+] B) = length A + length B"
by(auto simp: abc_comp.simps abc_shift.simps)
lemma abc_Hoare_plus_halt :
assumes A_halt : "⦃P⦄ (A::abc_prog) ⦃Q⦄"
and B_halt : "⦃Q⦄ (B::abc_prog) ⦃S⦄"
shows "⦃P⦄ (A [+] B) ⦃S⦄"
proof(rule_tac abc_Hoare_haltI)
fix lm
assume a: "P lm"
then obtain na lma where
"abc_final (abc_steps_l (0, lm) A na) A"
and b: "abc_steps_l (0, lm) A na = (length A, lma)"
and c: "Q abc_holds_for (length A, lma)"
using A_halt unfolding abc_Hoare_halt_def
by (metis (full_types) abc_final.simps abc_holds_for.simps prod.exhaust)
have "∃ n. abc_steps_l (0, lm) (A [+] B) n = (length A, lma)"
using abc_comp_first_steps_halt_eq b
by(simp)
then obtain nx where h1: "abc_steps_l (0, lm) (A [+] B) nx = (length A, lma)" ..
from c have "Q lma"
using c unfolding abc_holds_for.simps
by simp
then obtain nb lmb where
"abc_final (abc_steps_l (0, lma) B nb) B"
and d: "abc_steps_l (0, lma) B nb = (length B, lmb)"
and e: "S abc_holds_for (length B, lmb)"
using B_halt unfolding abc_Hoare_halt_def
by (metis (full_types) abc_final.simps abc_holds_for.simps prod.exhaust)
have h2: "abc_steps_l (length A, lma) (A [+] B) nb = (length B + length A, lmb)"
using d abc_comp_second_steps_eq
by simp
thus "∃n. abc_final (abc_steps_l (0, lm) (A [+] B) n) (A [+] B) ∧
S abc_holds_for abc_steps_l (0, lm) (A [+] B) n"
using h1 e
by(rule_tac x = "nx + nb" in exI, simp add: abc_steps_add)
qed
lemma abc_unhalt_append_eq:
assumes unhalt: "⦃P⦄ (A::abc_prog) ↑"
and P: "P args"
shows "abc_steps_l (0, args) (A [+] B) stp = abc_steps_l (0, args) A stp"
proof(induct stp)
case 0
thus "?case"
by(simp add: abc_steps_l.simps)
next
case (Suc stp)
have ind: "abc_steps_l (0, args) (A [+] B) stp = abc_steps_l (0, args) A stp"
by fact
obtain s nl where a: "abc_steps_l (0, args) A stp = (s, nl)"
by (metis prod.exhaust)
then have b: "s < length A"
using unhalt P
apply(auto simp: abc_Hoare_unhalt_def)
by (metis abc_notfinal.simps)
thus "?case"
using a ind
by(simp add: abc_step_red2 abc_step_l.simps abc_fetch.simps nth_append abc_comp.simps)
qed
lemma abc_Hoare_plus_unhalt1:
"⦃P⦄ (A::abc_prog) ↑ ⟹ ⦃P⦄ (A [+] B) ↑"
apply(rule abc_Hoare_unhaltI)
apply(subst abc_unhalt_append_eq,force,force)
by (metis (mono_tags, lifting) abc_notfinal.elims(3) abc_notfinal.simps add_diff_inverse_nat
abc_Hoare_unhalt_def le_imp_less_Suc length_abc_comp not_less_eq order_refl trans_le_add1)
lemma notfinal_all_before:
"⟦abc_notfinal (abc_steps_l (0, args) A x) A; y≤x ⟧
⟹ abc_notfinal (abc_steps_l (0, args) A y) A "
apply(subgoal_tac "∃ d. x = y + d", auto)
apply(cases "abc_steps_l (0, args) A y",simp)
apply(rule classical, simp add: abc_steps_add leI halt_steps2)
by arith
lemma abc_Hoare_plus_unhalt2':
assumes unhalt: "⦃Q⦄ (B::abc_prog) ↑"
and halt: "⦃P⦄ (A::abc_prog) ⦃Q⦄"
and notnull: "A ≠ []"
and P: "P args"
shows "abc_notfinal (abc_steps_l (0, args) (A [+] B) n) (A [+] B)"
proof -
obtain st nl stp where a: "abc_final (abc_steps_l (0, args) A stp) A"
and b: "Q abc_holds_for (length A, nl)"
and c: "abc_steps_l (0, args) A stp = (st, nl)"
using halt P unfolding abc_Hoare_halt_def
by (metis abc_holds_for.simps prod.exhaust)
obtain stpa where d:
"abc_notfinal (abc_steps_l (0, args) A stpa) A ∧ abc_final (abc_steps_l (0, args) A (Suc stpa)) A"
using abc_before_final[of args A stp,OF a notnull] by metis
thus "?thesis"
proof(cases "n < Suc stpa")
case True
have h: "n < Suc stpa" by fact
then have "abc_notfinal (abc_steps_l (0, args) A n) A"
using d
by(rule_tac notfinal_all_before, auto)
moreover then have "abc_steps_l (0, args) (A [+] B) n = abc_steps_l (0, args) A n"
using notnull
by(rule_tac abc_comp_first_steps_eq_pre, simp_all)
ultimately show "?thesis"
by(case_tac "abc_steps_l (0, args) A n", simp)
next
case False
have "¬ n < Suc stpa" by fact
then obtain d where i1: "n = Suc stpa + d"
by (metis add_Suc less_iff_Suc_add not_less_eq)
have "abc_steps_l (0, args) A (Suc stpa) = (length A, nl)"
using d a c
apply(case_tac "abc_steps_l (0, args) A stp", simp add: equal_when_halt)
by(case_tac "abc_steps_l (0, args) A (Suc stpa)", simp add: equal_when_halt)
moreover have "abc_steps_l (0, args) (A [+] B) stpa = abc_steps_l (0, args) A stpa"
using notnull d
by(rule_tac abc_comp_first_steps_eq_pre, simp_all)
ultimately have i2: "abc_steps_l (0, args) (A [+] B) (Suc stpa) = (length A, nl)"
using d
apply(case_tac "abc_steps_l (0, args) A stpa", simp)
by(simp add: abc_step_red2 abc_steps_l.simps abc_fetch.simps abc_comp.simps nth_append)
obtain s' nl' where i3:"abc_steps_l (0, nl) B d = (s', nl')"
by (metis prod.exhaust)
then have i4: "abc_steps_l (0, args) (A [+] B) (Suc stpa + d) = (length A + s', nl')"
using i2 apply(simp only: abc_steps_add)
using abc_comp_second_steps_eq[of nl B d s' nl']
by simp
moreover have "s' < length B"
using unhalt b i3
apply(simp add: abc_Hoare_unhalt_def)
apply(erule_tac x = nl in allE, simp)
by(erule_tac x = d in allE, simp)
ultimately show "?thesis"
using i1
by(simp)
qed
qed
lemma abc_comp_null_left[simp]: "[] [+] A = A"
proof(induct A)
case (Cons a A)
then show ?case
apply(cases a)
by(auto simp: abc_comp.simps abc_shift.simps)
qed (auto simp: abc_comp.simps abc_shift.simps)
lemma abc_comp_null_right[simp]: "A [+] [] = A"
proof(induct A)
case (Cons a A)
then show ?case
apply(cases a)
by(auto simp: abc_comp.simps abc_shift.simps)
qed (auto simp: abc_comp.simps abc_shift.simps)
lemma abc_Hoare_plus_unhalt2:
"⟦⦃Q⦄ (B::abc_prog)↑; ⦃P⦄ (A::abc_prog) ⦃Q⦄⟧⟹ ⦃P⦄ (A [+] B) ↑"
apply(case_tac "A = []")
apply(simp add: abc_Hoare_halt_def abc_Hoare_unhalt_def abc_exec_null)
apply(rule_tac abc_Hoare_unhaltI)
apply(erule_tac abc_Hoare_plus_unhalt2', simp)
apply(simp, simp)
done
end